Pendekatan Moderasi Beragama Dalam Menyikapi Judi Online: Upaya Pencegahan Dan Penanganan - Miftahussa'adah Wardi; Haifa Fitria Rahmawati; Muhammad Qodri Azizi; Farah Nur Latifah (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2024)
This study explores the effectiveness of religious moderation in addressing the rising challenge of online gambling in Sukamekar Village. As online gambling becomes increasingly accessible, its negative social and economic impacts are felt by local communities, posing threats to both individual welfare and communal harmony. Through qualitative methods—namely in-depth interviews with residents, observations of local community behavior, and an extensive literature review—the study investigates how religious principles emphasizing moderation, balance, and self-restraint can serve as deterrents to gambling habits. The findings reveal that core values within religious moderation, especially those advocating for self-control and an ethical lifestyle, resonate strongly within the community, discouraging engagement in gambling activities. Furthermore, support from families and proactive community involvement amplify the approach's impact, establishing a collective front against gambling. Collaboration among village authorities, religious leaders, family units, and community members emerges as crucial in cultivating a supportive environment that discourages gambling behaviors. In conclusion, the religious moderation approach not only provides a moral and cultural framework to counter online gambling but also fosters a pathway toward a more resilient, prosperous, and harmonious society in Sukamekar Village. This model highlights the broader potential for religiously informed community initiatives to address similar social issues in other settings.